PENGARUH MINAT MASYARAKAT TERHADAP PERILAKU PENCEGAHAN PENYAKIT DIABETES MELITUS - Togubu, Diana Mirja; Dirawan, Gufran D.; Pertiwi, Nurlita (Pascasarjana Universitas Negeri Makassar, 2023)
Diabetes Mellitus is a chronic disease caused by the failure of the pancreas to produce insulin hormone sufficiently, causing an increase in blood glucose levels. The type of research used is descriptive quantitative research by taking samples in three districts, namely Tamalanrea, Panakkukang and Tamalate with a total sample of 250 determined by purposive sampling. The results of the study show that people know the triggers for Diabetes Mellitus, but people still practice an irregular lifestyle or do not limit foods that can trigger Diabetes Mellitus.